Half-sandwich rare-earth metal complexes bearing a C5Me4-C6H4-o-CH2NMe2 ligand: synthesis, characterization and catalytic properties for isoprene, 1-hexene and MMA polymerization. Issue 48 (28th November 2019) - Song, Tingting; Liu, Ning; Tong, Xiaobo; Li, Feng; Mu, Xiaoyue; Mu, Ying
Abstract : New rare-earth metal complexes bearing the ligand C5 Me4 -C6 H4 - o -CH2 NMe2 were synthesized and studied as precatalysts for isoprene, 1-hexene and MMA polymerization. Abstract : A new ortho -dimethylaminomethylphenyl-tetramethylcyclopentadienyl ligand C5 Me4 H-C6 H4 - o -CH2 NMe2 (HL ) and a series of rare-earth metal complexes bearing this ligand were synthesized. Of these complexes, two binuclear alkyl complexes [(C5 Me4 -C6 H4 - o -CH2 N(Me)CH2 -μ)Ln(CH2 SiMe3 )]2 (Ln = Sc (1a ) and Y (1b )) were obtained from the alkane elimination reaction of the free ligand with Ln(CH2 SiMe3 )3 (THF)2, followed by an intramolecular C–H activation process of a NMe group in the ligand with a CH2 SiMe3 group, two binuclear dichloro complexes (C5 Me4 -C6 H4 - o -CH2 NMe2 )2 Y2 Cl4 [LiCl(THF)2 ] (2a ) and [(C5 Me4 -C6 H4 - o -CH2 NMe2 )LuCl(μ-Cl)]2 (2b ) were synthesized by the reaction of anhydrous yttrium or lutetium trichloride with the lithium salt of the ligand LiL, and the binuclear bis(borohydrido) complexes [(C5 Me4 -C6 H4 - o -CH2 NMe2 )Ln(μ-BH4 )BH4 ]2 (Ln = Sm (3a ) and Nd (3b )) were synthesized by the reaction of Ln(BH4 )3 (THF)3 (Ln = Sm and Nd) with the lithium salt of the ligand. The molecular structures of all complexes 1a, 1b, 2a, 2b, 3a and 3b were determined by single-crystal X-ray crystallography. Upon activation with AlR3 /Ph3 CB(C6 F5 )4, MAO or MMAO, the binuclear alkyl complexes 1a and 1b show good catalytic activity for isoprene cis -1, 4 enriched regioselective polymerization and moderate catalytic activity for 1-hexene polymerization. Complexes 3a and 3b were studied as catalysts for methyl methacrylate polymerization reaction under different conditions and were found to show moderate to high catalytic activity.